Analysis of Farmer’s Perception and Usage of Social Media in Agriculture - MadhuShekar, B. Raja; Rani, V. Sudha; Padmaveni, C.; Reddy, M. Malla; Kumar, B. Anil (International Journal of Bio-resource and Stress Management, 2023)
The present investigation was conducted during from June, 2021 to February, 2022 in twelve villages under District Agricultural Advisory and Transfer of Technology Centre, six each in Bhuvanagiri and Jangaon districts, Telangana, India to study the use of social media as a source of agricultural information, use pattern, preference towards different modes of information receiving and sharing, and frequency of use among farmers. The ex-post facto research design has been used for the study and samples were selected by using both purposive and random sampling techniques. The data was collected from 120 respondents through a structured interview schedule. The study revealed that 47.50% of the farmers were in the middle age group, 80.00% of them had high school and above education levels. 84.16% of the farmers used mobile phones and social media platforms for getting agriculture related information. 61.67% of the farmers used social networking sites like You tube, Twitter whereas 78.33% of the farmers used messaging platforms like Whatsapp, Telegram and Snapchat several times in a day. You tube was the preferred media out of all the social networking sites (67.50%), whatsapp for messaging (44.17%), You tube for media sharing (35.00%) and more than 90.00% of the farmers used Twitter for microblogging and none used blogs. The personal characteristics of the respondents’ such as education, farm size, social participation, scientific orientation, innovativeness, annual income, information seeking behaviour were significant and positively correlated while age and farming experience had significant but negative relationship with social media use.